Aias' Critical Day. Issue 1 (1st January 2021) - Cowan, Robert
Abstract : Calchas' prophecy in Sophocles' Aias that Athena's anger will pursue Aias for only "this one day" evokes the Hippocratic concept of the critical day, on which the patient might either die or survive. This is part of the wider engagement with Hippocratic ideas in Attic tragedy and has significant implications for the depiction of Aias' "second", metaphorical illness in the play. It places divine and physical explanations of illness in tension with each other. It also constructs the second illness as one of alienation that can be cured by reintegration into society, in contrast to Aias' own interpretation of it as one of shame that can only be cured by death.